3D Correlative Imaging of Lithium Ion Concentration in a Vertically Oriented Electrode Microstructure with a Density Gradient. Issue 16 (11th April 2022) - Huang, Chun; Wilson, Matthew D.; Suzuki, Kosuke; Liotti, Enzo; Connolley, Thomas; Magdysyuk, Oxana V.; Collins, Stephen; Van Assche, Frederic; Boone, Matthieu N.; Veale, Matthew C.; Lui, Andrew; Wheater, Rhian‐Mair; et al.
Abstract: The performance of Li + ion batteries (LIBs) is hindered by steep Li + ion concentration gradients in the electrodes. Although thick electrodes (≥300 µm) have the potential for reducing the proportion of inactive components inside LIBs and increasing battery energy density, the Li + ion concentration gradient problem is exacerbated. Most understanding of Li + ion diffusion in the electrodes is based on computational modeling because of the low atomic number ( Z ) of Li. There are few experimental methods to visualize Li + ion concentration distribution of the electrode within a battery of typical configurations, for example, coin cells with stainless steel casing. Here, for the first time, an interrupted in situ correlative imaging technique is developed, combining novel, full‐field X‐ray Compton scattering imaging with X‐ray computed tomography that allows 3D pixel‐by‐pixel mapping of both Li + stoichiometry and electrode microstructure of a LiNi0.8 Mn0.1 Co0.1 O2 cathode to correlate the chemical and physical properties of the electrode inside a working coin cell battery. An electrode microstructure containing vertically oriented pore arrays and a density gradient is fabricated. It is shown how the designed electrode microstructure improves Li + ion diffusivity, homogenizes Li + ion concentration through the ultra‐thick electrode (1 mm), and improves utilization of electrode active materials. Abstract : An interrupted in situ correlative imaging technique is developed, combining novel, full‐field X‐ray Compton scattering imaging with complementary X‐ray computed tomography that allows 3D pixel‐by‐pixel mapping of both Li + stoichiometry and electrode microstructure of a LiNi0.8 Mn0.1 Co0.1 O2 cathode to cross‐correlate the chemical and physical properties of the electrode inside a working coin cell battery.